NATURAL RESOURCES CONTRIBUTION IN DEFENSE DIPLOMACY: A CASE STUDY OF BRUNEI DARUSSALAM - Marina Ika Sari (Jurnal Pertahanan & Bela Negara, 2019)
Brunei Darussalam is a country rich of natural resources, especially oil and natural gas. The country's income source is highly dependent on oil and gas sector. The fall of world oil price had an impact on Brunei Darussalam’s economy and the government decided to cut off 25% of its defense budget in 2015. However, in 2018, Brunei Darussalam's defense budget reached B$ 492,754,700, a 12.9% increase from the previous year's budget. This research focuses on Brunei Darussalam’s oil and natural gas sectors which have an impact on its defense budget. The amount of a country's defense budget will affect its defense power, including its defense diplomacy activities. This study employs the concept of defense diplomacy. This study finds that there are several key results areas in the defense of Brunei Darussalam government, such as territorial integrity, support toward "whole-of-nation" approach, effective defence diplomacy, military involvement in international missions, high standard of human resource capacity, as well as respected and credible image of the defense organisation.Keywords: Brunei Darussalam, defense diplomacy, natural resources